Analisis Chat GPT untuk Mendukung Proses Belajar Mahasiswa Ilmu Komunikasi Semester Akhir UIN Sumatera Utara Medan - Afriansyah, Wisnu; Matondang, Muhammad Alfikri (Ideas Publishing, 2024)
Chat-GPT has changed communication, information access, and student education, therefore UINSU Medan communication science students must adapt quickly to AI in learning. This research examines how Chat-GPT enhances UINSU students' learning. This research uses quantitative descriptive method. This survey sampled UINSU Communication Science students. The results showed Chat GPT provides correct, simple data. In-depth content helps academic projects and arguments, although it might be better. Strong and responsive, this platform simplifies learning. Academically relevant and personalized GPT Chat comments demonstrate adaptability. Use improves critical thinking. Happy users learn well. GPT speeches boost learning and competencies. Many responders offered favorable feedback, however some portions need updating